2013
DOI: 10.1515/humor-2013-0028
|View full text |Cite
|
Sign up to set email alerts
|

Humor preference and the Autism Quotient in an undergraduate sample

Abstract: Most previous studies relating autism and humor have compared responses to jokes or cartoons in autistic children and controls. The present study used the Humor Appreciation Measure (HAM, Rawlings 2008), which measures responses to hypothetical real life situations, as well as jokes; and employed the Autism-spectrum Quotient (AQ, Baron-Cohen et al. 1995), a self-report instrument which assumes that autism exists on a continuum. In an undergraduate sample (N = 126), substantial correlations were reported betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…As the present population consisted of healthy people with autistic traits without a diagnosis of ASD, this study shows that impairment in ToM and humor extends to the healthy population with autistic traits. In support of this, differences in humor styles and appreciation have been reported among healthy individuals with autistic traits ( Eriksson, 2013 ; Rawlings, 2013 ). For ToM impairment in healthy individuals, variation was shown by an implicit test: the Reading the Mind in the Eyes test.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…As the present population consisted of healthy people with autistic traits without a diagnosis of ASD, this study shows that impairment in ToM and humor extends to the healthy population with autistic traits. In support of this, differences in humor styles and appreciation have been reported among healthy individuals with autistic traits ( Eriksson, 2013 ; Rawlings, 2013 ). For ToM impairment in healthy individuals, variation was shown by an implicit test: the Reading the Mind in the Eyes test.…”
Section: Discussionsupporting
confidence: 54%
“…Consistent with this view, studies examining autistic traits in the healthy population have been increasing in recent years. In addition, studies demonstrating differences in humor styles and appreciation ( Eriksson, 2013 ; Rawlings, 2013 ) among healthy people with autistic traits similar to those in the ASD population have been reported.…”
Section: Introductionmentioning
confidence: 92%
“…However, previous studies have not found a U-shaped relationship between the severity of ASD characteristics and humor appreciation. For instance, a previous study by Rawlings (2013) found a primary linear relationship between the severity of ASD characteristics and humor appreciation in a sample of 126 typically developing individuals. The reason for this result may be that Rawlings (2013) hypothesized that there is a primary linear relation between ASD characteristic severity and appreciation of humor.…”
Section: Introductionmentioning
confidence: 95%
“…For instance, a previous study by Rawlings (2013) found a primary linear relationship between the severity of ASD characteristics and humor appreciation in a sample of 126 typically developing individuals. The reason for this result may be that Rawlings (2013) hypothesized that there is a primary linear relation between ASD characteristic severity and appreciation of humor. In other words, this research suggested that U-shaped relationship between the severity of ASD characteristics and humor appreciation is valid.…”
Section: Introductionmentioning
confidence: 95%
“…(Garner, 2006, p. 178 He claims that elementary-level students can benefit from the use of the first type, intermediate students will appreciate universal humor plus some types of culture-base jokes, and advanced students can benefit from and appreciate all three types. Wagner and Urios-Aparisi (2011) stated wordplay is an example of a type of humor that is often cited as difficult and best reserved for those of advanced proficiency (Berwald, 1992;Deneire, 1995;Rawlings, 2013).…”
Section: Mel Brooks Wrote "Tragedy Is When I Cut My Finger Comedy Imentioning
confidence: 99%